Two mechanisms of hydrodynamic lubrication in textured bearings - Fowell,MT; Olver,AV; Pegg,IG; Spikes,HA (2006)
There is currently great interest in the use of textured bearings, where many tiny micropockets are incorporated in one of the bearing surfaces. Such texturing has been found to enhance load support and to reduce hydrodynamic friction in low load conditions, when the two surfaces have very low or zero convergence ratio, i.e. are essentially parallel. It is not immediately clear from hydrodynamic lubrication theory how a bearing with parallel surfaces and internal pockets can entrain any lubricant to form a hydrodynamic film and thus support load. However in a recent technical note the authors have shown that the occurrence of cavitation within micropockets results in suction of lubricant into the bearing, because the pressure inside the pockets is less than the surrounding, atmospheric pressure [1]. For parallel or very low convergence ratio bearings, this supply process replaces fluid entrainment as the main mechanism by which lubricant is drawn into the contact. In previous work this suction mechanism was demonstrated using a simple analytical approach for a 1D parallel bearing having a single pocket. The current paper extends this analytical method to convergent bearings having a single pocket and then applies a numerical solution of the first order Reynolds equation to solve for flow in multi-pocketed bearings. This enables the contribution of fluid suction on the load support of low convergence ratio bearings to be investigated. Copyright © 2006 by ASME.